Thin flexographic printing cold stamping material and preparation process thereof
By using the composite acrylic resin and modified polybine oxylene oxide and other raw materials to prepare the imaging layer, the imaging layer of the soft seal cold -scald material is poor, easy to wear and flame retardant performance, and realize the high adhesion, flame retardant properties And abrasion -resistant thin -type soft printing ingredients.
Patent Information
- Application Number
- CN202411499772.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-25
AI Technical Summary
In the application of existing flexographic cold ironing materials, there are problems such as poor adhesion, easy wear and insufficient flame retardant performance of imaging layers, especially in products that require high safety standards, which are difficult to effectively solve.
Use composite acrylic resin, modified polyethylene oxide, pigment, ethanol, water, puppet couplet, nano -sanxide, etc. to prepare the imaging layer, and through specific process steps and response conditions Flequanis and abrasion -resistant thin -sealing cold scalding materials.
It significantly improves the adhesion and flame retardant properties of the imaging layer on the aluminum coating, enhances the wear resistance, thereby improving the appearance quality and safety of the product.
Abstract
Description
Technical Field
[0002] The invention relates to the technical field of cold stamping materials, in particular to a thin flexographic cold stamping material and a preparation process thereof. Background Art
[0004] With the development of printing technology, flexographic cold foil technology has been widely used in the field of packaging printing due to its high efficiency and environmental protection. However, in actual application, the imaging layer containing ink often has problems such as poor adhesion and easy wear. These problems not only affect the appearance quality of the product, but also may lead to inaccurate information transmission. Especially for products that require higher safety standards, the insufficient flame retardant performance of the imaging layer is also a problem that needs to be solved urgently.
[0005] Some flexographic cold stamping materials currently used in the market will have poor fastness of the imaging layer when used with certain types of inks. This phenomenon occurs mainly due to the compatibility problem between the characteristics of the flexographic hot stamping materials themselves and the ink used in the imaging layer. Specifically, the interaction between the ink and the aluminum coating is insufficient, resulting in the imaging layer being easily detached or worn. In addition, when the product needs to meet the requirements of use in a specific environment (such as fire protection requirements), existing materials often cannot provide sufficient protection.
[0006] Therefore, developing a thin flexographic cold foil material can improve the above problems and enhance the adhesion, flame retardancy and wear resistance of the imaging layer, which is of great significance for improving product quality and market competitiveness. This will not only help meet the growing demand for personalized packaging, but also help promote the printing industry to develop in a higher quality direction. Summary of the invention
[0008] The purpose of the present invention is to provide a method to solve the technical problems mentioned in the above background technology.
[0009] The technical solution for achieving the purpose of the present invention is:
[0010] A thin flexographic cold stamping material comprises, from bottom to top, a base film layer, a release layer, an imaging layer, an aluminum-plated layer, and a glue layer. The imaging layer comprises, by weight, 30 to 40 parts by weight of composite acrylic resin, 6 to 12 parts by weight of modified polyepichlorohydrin, 0.2 to 0.3 parts by weight of pigment, 3 to 4 parts by weight of ethanol, 47 to 48 parts by weight of water, 2 to 3 parts by weight of coupling agent, and 2 to 3 parts by weight of nano-silicon dioxide.
[0011] Furthermore, the composite acrylic resin is obtained by copolymerization of 2,4,6-tri(allyloxy)-1,3,5-triazine, acrylic acid, butyl acrylate, diallylamine hydrochloride, methyl methacrylate, and hydroxyethyl methacrylate.
[0012] Furthermore, the modified polyepichlorohydrin is obtained by reacting POSS with epichlorohydrin.
[0013] The present invention also provides a preparation process for a thin flexographic cold stamping material, comprising the following steps: firstly coating a release coating on a base film layer and then drying it, then coating an imaging layer coating on the release coating and then drying it, then vacuum-plating aluminum on the imaging layer, and finally coating an adhesive layer coating on the aluminum-plated layer and then drying it to form a thin flexographic cold stamping material.
[0014] Furthermore, the preparation method of the imaging layer coating is as follows:
[0015] Under inert gas protection, 30-40 parts by mass of composite acrylic resin, 6-12 parts by mass of modified polyepichlorohydrin, 0.2-0.3 parts by mass of pigment, 3-4 parts by mass of ethanol, 47-48 parts by mass of water, 2-3 parts by mass of coupling agent, 2-3 parts by mass of nano-silicon dioxide, and 0.08-0.12 parts by mass of emulsifier are charged into a reaction container, and a high-speed homogenizer is used to disperse the ink at 500-700 r / min for 10-20 min until the ink is uniformly mixed, and then the temperature is raised to 69-71°C, stirred for reaction for 4.5-5.5h, cooled to room temperature, and adjusted to pH 8.0-9.0 by adding 25%-28% ammonia water to obtain an imaging layer coating.
[0016] Furthermore, the coupling agent includes silane coupling agent KH-560.
[0017] Further, the preparation steps of the composite acrylic resin are as follows: 0.4-0.6 mass parts of 2,4,6-tri(allyloxy)-1,3,5-triazine, 0.06-0.08 mass parts of acrylic acid, 0.08-0.12 mass parts of butyl acrylate, 2-3 mass parts of diallylamine hydrochloride, 2-3 mass parts of methyl methacrylate, and 2-3 mass parts of hydroxyethyl methacrylate are mixed uniformly to obtain a monomer mixture; 25-35% of the monomer mixture is added to the mixture; The combined liquid, 0.002-0.0024 parts by weight of initiator and 30-50 parts by weight of isopropanol are stirred and mixed, and the temperature is raised to reflux while stirring. Subsequently, the remaining monomer mixed liquid, 0.008-0.0096 parts by weight of initiator and 30-50 parts by weight of isopropanol are added dropwise. After 1.8-2.2 hours, the addition is stopped, and the reaction is continued by keeping the temperature for 3 hours. Ammonia water with a concentration of 25%-28% is added to adjust the pH to 8.0-9.0 to obtain a composite acrylic resin.
[0018] Furthermore, the preparation method of the modified polyepichlorohydrin is as follows: 92-94 parts by mass of heptaphenylsilsesquioxane trisilanol and 500 parts by mass of solvent dichloromethane are stirred and mixed for 1-3 hours until the heptaphenylsilsesquioxane trisilanol is dissolved, 70.6-71 parts by mass of catalyst boron trifluoride ether is added at room temperature and stirring is continued for 30 minutes, then the temperature is lowered to 17.5-18.5°C, 93-372 parts by mass of epichlorohydrin are added dropwise, and the addition is completed within 1.8-2.2 hours, and then the temperature is raised to 39-41°C and stirring is continued for 4 hours, then, it is washed with saturated sodium bicarbonate solution until it is alkaline, and then washed with deionized water until it is neutral, and the unreacted catalyst is removed, and then it is distilled under reduced pressure at 109-111°C for 1.8-2.2 hours to remove the solvent and small molecule compounds to obtain modified polyepichlorohydrin.
[0019] By adopting the above technical solution, the present invention has the following beneficial effects:
[0020] (1) The present invention adopts composite acrylic resin, modified polyepichlorohydrin, pigment, ethanol, water, coupling agent and nano-silicon dioxide as raw materials to prepare the imaging layer; wherein the polyepichlorohydrin in the modified polyepichlorohydrin has good adhesion and flame retardancy, and adding the modified polyepichlorohydrin to the imaging layer can effectively improve the adhesion of the imaging layer on the aluminum-plated layer and make the imaging layer have good flame retardancy.
[0021] (2) The composite acrylic resin of the present invention is obtained by copolymerization of 2,4,6-tri(allyloxy)-1,3,5-triazine, acrylic acid, butyl acrylate, diallylamine hydrochloride, methyl methacrylate, and hydroxyethyl methacrylate, wherein 2,4,6-tri(allyloxy)-1,3,5-triazine, as a multifunctional monomer, has three allyl groups and can form a dense cross-linked network during the polymerization process; these cross-linking points enhance the mechanical strength and thermal stability of the composite acrylic resin, so that it can still maintain good performance under high temperature or stress conditions; acrylic acid, hydroxyethyl methacrylate, and diallylamine hydrochloride all contain hydrophilic groups, which can form hydrogen bonds or other types of chemical bonds with the aluminum-plated layer, thereby improving the bonding force between the composite acrylic resin and the aluminum-plated layer.
[0022] (3) The present invention adopts POSS heptaphenylsilsesquioxane trisilanol to react with epichlorohydrin to prepare modified polyepichlorohydrin. The silanol groups in POSS heptaphenylsilsesquioxane trisilanol can undergo ring-opening reaction polymerization with the epoxy groups in epichlorohydrin, and POSS is embedded in the main chain of polyepichlorohydrin to form rigid sites. These rigid sites can effectively resist external forces, reduce the slippage between molecular chains, improve the hardness of the modified polyepichlorohydrin, and thus improve the wear resistance of the imaging layer.
[0023] (4) The present invention compounds raw material components such as composite acrylic resin and modified polyepichlorohydrin. When the modified polyepichlorohydrin is mixed with the composite acrylic resin containing a secondary amine group, the chlorine atoms in the modified polyepichlorohydrin react with the secondary amine groups in the composite acrylic resin by a nucleophilic substitution reaction. Specifically, the nitrogen atoms in the secondary amine groups act as nucleophilic reagents to attack the chlorine atoms in the modified polyepichlorohydrin to form quaternary ammonium cations. When preparing a thin flexographic cold stamping material, the polar heads of the quaternary ammonium cations in the imaging layer and the metal surface of the aluminum-plated layer form an interaction force, thereby further enhancing the adhesion of the imaging layer to the aluminum-plated layer. DETAILED DESCRIPTION
[0025] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with specific implementation methods.
[0026] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0027] The raw materials of the embodiments and comparative examples of the present invention are as follows:
[0028] Release coating: Add ethanol and water into a stirring bucket according to the formula ratio, stir evenly at a constant temperature of 28°C for 10 minutes, then add the water-based oxidized polyethylene wax emulsion into the stirring bucket according to the proportion, stir while adding, and continue stirring for 45 minutes after adding to obtain the release coating;
[0029] The base film layer uses 6U BOPET film;
[0030] The preparation steps of the adhesive layer coating are as follows: 40 parts by weight of xylene are put into a reaction container, and the temperature is raised to 84° C. while stirring, and then a mixture of 2.5 parts by weight of methyl methacrylate, 2 parts by weight of hydroxyethyl methacrylate, 2 parts by weight of butyl acrylate, 2 parts by weight of glycidyl acrylate, and 0.01 parts by weight of initiator azobisisobutyronitrile is added dropwise, and the addition is completed after 3 hours, and the heat preservation reaction is continued for 3 hours to obtain an adhesive layer resin base material; 20 parts by weight of xylene are added into a stirring barrel, and the mixture is stirred evenly at a constant temperature of 25° C. for 5 minutes, and then 60 parts by weight of the adhesive layer resin base material are added into the stirring barrel, and the mixture is stirred while being added, and the stirring is continued for 30 minutes after the addition is completed to obtain an adhesive layer coating;
[0031] The coupling agent is silane coupling agent KH-560;
[0032] The emulsifier used is OP-10;
[0033] The pigment used is phthalocyanine blue;
[0034] (Example 1)
[0035] A preparation process for a thin flexographic cold stamping material comprises the following steps: firstly coating a 0.3 μm thick release coating on a base film layer and then drying it, then coating a 0.3 μm thick imaging layer coating on the release coating and then drying it, then coating an aluminum coating with a thickness of 240 angstroms on the imaging layer, and finally coating a 0.3 μm thick glue layer coating on the aluminum coating and then drying it to form a thin flexographic cold stamping material.
[0036] The preparation method of the imaging layer coating is as follows:
[0037] Under inert gas protection, 30 parts by mass of composite acrylic resin, 6 parts by mass of modified polyepichlorohydrin, 0.2 parts by mass of pigment, 3 parts by mass of ethanol, 47 parts by mass of water, 2 parts by mass of coupling agent, 2 parts by mass of nano-silicon dioxide, and 0.08 parts by mass of emulsifier were charged into a reaction container, and dispersed at 500 r / min for 10 minutes using a high-speed homogenizer until the ink was evenly mixed. The temperature was then raised to 69°C, stirred for reaction for 4.5 hours, cooled to room temperature, and 25% ammonia water was added to adjust the pH to 8.0 to obtain an imaging layer coating.
[0038] The preparation steps of the composite acrylic resin are as follows: 0.4 parts by mass of 2,4,6-tri(allyloxy)-1,3,5-triazine, 0.06 parts by mass of acrylic acid, 0.08 parts by mass of butyl acrylate, 2 parts by mass of diallylamine hydrochloride, 2 parts by mass of methyl methacrylate, and 2 parts by mass of hydroxyethyl methacrylate are uniformly mixed to obtain a monomer mixture; 25% of the monomer mixture, 0.002 parts by mass of an initiator, and 30 parts by mass of isopropanol are stirred and mixed, and the mixture is heated to reflux while stirring, and then the remaining monomer mixture, 0.008 parts by mass of an initiator, and 30 parts by mass of isopropanol are dripped, and the dripping is completed after 1.8 hours, and the reaction is kept warm for 3 hours, and ammonia water with a concentration of 25% is adjusted to pH 8.0 to obtain a composite acrylic resin.
[0039] The preparation method of the modified polyepichlorohydrin is as follows: 92 parts by mass of heptaphenylsilsesquioxane trisilanol and 500 parts by mass of solvent dichloromethane are stirred and mixed for 1 hour until the heptaphenylsilsesquioxane trisilanol is dissolved, 70.6 parts by mass of catalyst boron trifluoride ether is added at room temperature and stirring is continued for 30 minutes, then the temperature is lowered to 17.5° C., 93 parts by mass of epichlorohydrin is added dropwise, and the addition is completed within 1.8 hours, then the temperature is raised to 39° C. and stirring is continued for 4 hours, then the mixture is washed with a saturated sodium bicarbonate solution until it is alkaline, and then washed with deionized water until it is neutral, and the unreacted catalyst is removed, and then the mixture is distilled under reduced pressure at 109° C. for 1.8 hours to remove the solvent and small molecular compounds to obtain the modified polyepichlorohydrin.
[0040] Example 2
[0041] A preparation process for a thin flexographic cold stamping material comprises the following steps: firstly coating a 0.3 μm thick release coating on a base film layer and then drying it, then coating a 0.3 μm thick imaging layer coating on the release coating and then drying it, then coating an aluminum coating with a thickness of 240 angstroms on the imaging layer, and finally coating a 0.3 μm thick glue layer coating on the aluminum coating and then drying it to form a thin flexographic cold stamping material.
[0042] The preparation method of the imaging layer coating is as follows:
[0043] Under inert gas protection, 35 parts by mass of composite acrylic resin, 9 parts by mass of modified polyepichlorohydrin, 0.25 parts by mass of pigment, 3.5 parts by mass of ethanol, 47.5 parts by mass of water, 2.5 parts by mass of coupling agent, 2.5 parts by mass of nano-silicon dioxide, and 0.01 parts by mass of emulsifier were charged into a reaction container, and a high-speed homogenizer was used to disperse the ink at 600 r / min for 15 min until the ink was evenly mixed. The temperature was then raised to 70°C, stirred for reaction for 5 hours, cooled to room temperature, and the pH was adjusted to 8.5 by adding 26% ammonia water to obtain an imaging layer coating.
[0044] The preparation steps of the composite acrylic resin are as follows: 0.5 parts by mass of 2,4,6-tri(allyloxy)-1,3,5-triazine, 0.07 parts by mass of acrylic acid, 0.1 parts by mass of butyl acrylate, 2.5 parts by mass of diallylamine hydrochloride, 2.5 parts by mass of methyl methacrylate, and 2.5 parts by mass of hydroxyethyl methacrylate are uniformly mixed to obtain a monomer mixture; 30% of the monomer mixture, 0.0022 parts by mass of an initiator, and 40 parts by mass of isopropanol are stirred and mixed, and the mixture is heated to reflux while stirring, and then the remaining monomer mixture, 0.0088 parts by mass of an initiator, and a mixture of 40 parts by mass of isopropanol are dripped, and the dripping is stopped after 2 hours, and the reaction is kept warm for 3 hours, and ammonia water with a concentration of 26% is added to adjust the pH to 8.5 to obtain a composite acrylic resin.
[0045] The preparation method of the modified polyepichlorohydrin is as follows: 93 parts by mass of heptaphenylsilsesquioxane trisilanol and 500 parts by mass of solvent dichloromethane are stirred and mixed for 2 hours until the heptaphenylsilsesquioxane trisilanol is dissolved, 70.8 parts by mass of catalyst boron trifluoride ether is added at room temperature and stirring is continued for 30 minutes, then the temperature is lowered to 18° C., 233 parts by mass of epichlorohydrin is added dropwise, and the addition is completed within 2 hours, then the temperature is raised to 40° C. and stirring is continued for 4 hours, then the mixture is washed with a saturated sodium bicarbonate solution until it is alkaline, and then washed with deionized water until it is neutral, and the unreacted catalyst is removed, and then the mixture is distilled under reduced pressure at 110° C. for 2 hours to remove the solvent and small molecular compounds to obtain the modified polyepichlorohydrin.
[0046] Example 3
[0047] A preparation process for a thin flexographic cold stamping material comprises the following steps: firstly coating a 0.3 μm thick release coating on a base film layer and then drying it, then coating a 0.3 μm thick imaging layer coating on the release coating and then drying it, then coating an aluminum coating with a thickness of 240 angstroms on the imaging layer, and finally coating a 0.3 μm thick glue layer coating on the aluminum coating and then drying it to form a thin flexographic cold stamping material.
[0048] The preparation method of the imaging layer coating is as follows:
[0049] Under inert gas protection, 40 parts by mass of composite acrylic resin, 12 parts by mass of modified polyepichlorohydrin, 0.3 parts by mass of pigment, 4 parts by mass of ethanol, 48 parts by mass of water, 3 parts by mass of coupling agent, 3 parts by mass of nano-silicon dioxide, and 0.12 parts by mass of emulsifier were charged into a reaction container, and a high-speed homogenizer was used to disperse the ink at 700 r / min for 20 min until the ink was evenly mixed. The temperature was then raised to 71°C, stirred for reaction for 5.5 hours, cooled to room temperature, and 28% ammonia water was added to adjust the pH to 9.0 to obtain an imaging layer coating.
[0050] The preparation steps of the composite acrylic resin are as follows: 0.6 parts by mass of 2,4,6-tri(allyloxy)-1,3,5-triazine, 0.08 parts by mass of acrylic acid, 0.12 parts by mass of butyl acrylate, 3 parts by mass of diallylamine hydrochloride, 3 parts by mass of methyl methacrylate, and 3 parts by mass of hydroxyethyl methacrylate are uniformly mixed to obtain a monomer mixture; 35% of the monomer mixture, 0.0024 parts by mass of an initiator, and 50 parts by mass of isopropanol are stirred and mixed, and the mixture is heated to reflux while stirring, and then the remaining monomer mixture, 0.0096 parts by mass of an initiator, and a mixture of 50 parts by mass of isopropanol are dripped, and the dripping is stopped after 2.2 hours, and the reaction is kept warm for 3 hours, and ammonia water with a concentration of 28% is added to adjust the pH to 9.0 to obtain a composite acrylic resin.
[0051] The preparation method of the modified polyepichlorohydrin is as follows: 94 parts by mass of heptaphenylsilsesquioxane trisilanol and 500 parts by mass of solvent dichloromethane are stirred and mixed for 3 hours until the heptaphenylsilsesquioxane trisilanol is dissolved, 71 parts by mass of catalyst boron trifluoride ether is added at room temperature and stirring is continued for 30 minutes, then the temperature is lowered to 18.5° C., 372 parts by mass of epichlorohydrin is added dropwise, and the addition is completed within 2.2 hours, then the temperature is raised to 41° C. and stirring is continued for 4 hours, then, the mixture is washed with a saturated sodium bicarbonate solution until it is alkaline, and then washed with deionized water until it is neutral, and the unreacted catalyst is removed, and then the mixture is distilled under reduced pressure at 111° C. for 2.2 hours to remove the solvent and small molecular compounds to obtain the modified polyepichlorohydrin.
[0052] Comparative Example 1
[0053] The difference between Comparative Example 1 and Example 2 is that the composite acrylic resin is obtained by copolymerization of acrylic acid, butyl acrylate, diallylamine hydrochloride, methyl methacrylate, and hydroxyethyl methacrylate, and the remaining steps and components are the same as those of Example 2.
[0054] Comparative Example 2
[0055] The difference between Comparative Example 2 and Example 2 is that the composite acrylic resin is obtained by copolymerization of 2,4,6-tri(allyloxy)-1,3,5-triazine, acrylic acid, butyl acrylate, methyl methacrylate, and hydroxyethyl methacrylate, and the remaining steps and components are the same as those of Example 2.
[0056] Comparative Example 3
[0057] The difference between Comparative Example 3 and Example 2 is that the composite acrylic resin is obtained by copolymerization of acrylic acid, butyl acrylate, methyl methacrylate and hydroxyethyl methacrylate, and the remaining steps and components are the same as those of Example 2.
[0058] Comparative Example 4
[0059] The difference between Comparative Example 4 and Example 2 is that the raw material components of the imaging layer only use composite acrylic resin, polyepichlorohydrin, pigment, ethanol, water, coupling agent, and nano-silicon dioxide; the remaining steps and components are the same as those of Example 2.
[0060] Comparative Example 5
[0061] The difference between Comparative Example 5 and Example 2 is that the raw material components of the imaging layer only use composite acrylic resin, pigment, ethanol, water, coupling agent, and nano-silicon dioxide; the remaining steps and components are the same as those of Example 2.
[0062] Comparative Example 6
[0063] The difference between Comparative Example 6 and Example 2 is that the raw material components of the imaging layer only use composite acrylic resin, heptaphenylsilsesquioxane trisilanol, pigment, ethanol, water, coupling agent, and nano-silica; the remaining steps and components are the same as Example 2.
[0064] Effect example
[0065] Adhesion: According to GB / T1720-88 paint film adhesion determination method standard, the adhesion of the imaging layer of the thinned flexographic cold stamping materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 on the aluminized layer was measured using a QFD electric paint film adhesion tester, and the firmness of the adhesion of the imaging layer to the aluminized layer was evaluated according to 7 levels, with the higher the level, the lower the adhesion.
[0066] Hardness: According to GB / T 6739-2006 Paint and varnish, pencil method for determining the hardness of paint film, the hardness of the imaging layer is measured; the tip of the pencil inserted into the hand-pushed pencil hardness tester cart should be at a 45° angle to the surface of the imaging layer, and the imaging layer is tested under a 500g weight load.
[0067] The following table shows the performance data of the thin flexographic cold stamping materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6:
[0068] Adhesion grade hardness Example 1 1 5H Example 2 1 5H Example 3 1 5H Comparative Example 1 2 4H Comparative Example 2 4 5H Comparative Example 3 4 4H Comparative Example 4 2 2H Comparative Example 5 3 2H Comparative Example 6 4 5H
[0069] From the comparison of the data of the embodiments and the comparative examples in the above table, it can be seen that the imaging layer of the thinned flexographic cold stamping material prepared in the embodiments has good adhesion and good wear resistance; the difference between comparative example 1 and embodiment 2 is that the composite acrylic resin of embodiment 2 further adds 2,4,6-tri(allyloxy)-1,3,5-triazine, and the introduction of 2,4,6-tri(allyloxy)-1,3,5-triazine improves the crosslinking density of the composite acrylic resin. In addition, the introduction of the rigid triazine ring not only improves the adhesion of the imaging layer, but also improves the wear resistance of the imaging layer.
[0070] The difference between Comparative Example 2 and Example 2 is that the composite acrylic resin of Example 2 further introduces diallylamine hydrochloride, which contains hydrophilic groups that can form hydrogen bonds or other types of chemical bonds with the aluminum-plated layer, thereby improving the adhesion between the composite acrylic resin and the aluminum-plated layer; and the secondary amine in the composite acrylic resin can also react with the chlorine atoms in the modified polyepichlorohydrin to form a quaternary ammonium salt, and the positively charged property of the quaternary ammonium salt generates an electrostatic attraction between the metal surface of the aluminum-plated layer with a slight negative charge, and at the same time, the nitrogen atoms in the quaternary ammonium cation can also form coordination bonds with the unpaired electrons on the surface of the aluminum-plated layer to achieve chemical adsorption. The synergistic effects of these electrostatic attraction, chemical adsorption and other interaction forces jointly significantly enhance the adhesion between the imaging layer and the aluminum-plated layer, making it difficult for the imaging layer to be peeled off from the aluminum-plated layer when subjected to external mechanical stress.
[0071] The difference between Comparative Example 3 and Example 2 is that the composite acrylic resin of Example 2 further introduces 2,4,6-tri(allyloxy)-1,3,5-triazine and diallylamine hydrochloride, and the imaging layer of the obtained thin flexographic cold stamping material has better adhesion.
[0072] The difference between Comparative Examples 4 and 5 and Example 2 is that the raw material components of the imaging layer of Example 2 further introduce polyepichlorohydrin modified with heptaphenylsilsesquioxane trisilanol. The introduction of polyepichlorohydrin modified with heptaphenylsilsesquioxane trisilanol, on the one hand, introduces rigid sites of heptaphenylsilsesquioxane trisilanol to increase the wear resistance of the imaging layer; on the other hand, polyepichlorohydrin has good viscosity, and the chlorine atoms in the modified polyepichlorohydrin react with the secondary amines in the composite acrylic resin to form quaternary ammonium salts. The positively charged characteristics of the quaternary ammonium salts generate electrostatic attraction with the metal surface of the aluminum-plated layer with a slight negative charge. At the same time, the nitrogen atoms in the quaternary ammonium cations can also form coordination bonds with unpaired electrons on the surface of the aluminum-plated layer to achieve chemical adsorption. The synergistic effects of these electrostatic attraction, chemical adsorption and other interaction forces jointly significantly enhance the adhesion between the imaging layer and the aluminum-plated layer, so that the imaging layer is not easily peeled off from the aluminum-plated layer when subjected to external mechanical stress.
[0073] The difference between Comparative Example 6 and Example 2 is that polyepichlorohydrin is further introduced into the raw material components of the imaging layer of Example 2. The polyepichlorohydrin has good viscosity, and the chlorine atoms in the modified polyepichlorohydrin react with the secondary amine in the composite acrylic resin to form a quaternary ammonium salt. The positively charged property of the quaternary ammonium salt generates an electrostatic attraction with the metal surface of the aluminum-plated layer with a slight negative charge. At the same time, the nitrogen atoms in the quaternary ammonium cation can also form coordination bonds with the unpaired electrons on the surface of the aluminum-plated layer to achieve chemical adsorption. The synergistic effects of these electrostatic attraction, chemical adsorption and other interaction forces significantly enhance the adhesion between the imaging layer and the aluminum-plated layer, making it difficult for the imaging layer to be peeled off from the aluminum-plated layer when subjected to external mechanical stress.
[0074] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A thin flexographic cold stamping material, comprising, from bottom to top, a base film layer, a release layer, an imaging layer, an aluminum plating layer, and a glue layer, characterized in that: The imaging layer comprises, by weight, 30-40 parts of composite acrylic resin, 6-12 parts of modified polyepichlorohydrin, 0.2-0.3 parts of pigment, 3-4 parts of ethanol, 47-48 parts of water, 2-3 parts of coupling agent and 2-3 parts of nano-silicon dioxide.
2. The thin flexographic cold stamping material according to claim 1, characterized in that: The composite acrylic resin is obtained by copolymerizing 2,4,6-tri(allyloxy)-1,3,5-triazine, acrylic acid, butyl acrylate, diallylamine hydrochloride, methyl methacrylate and hydroxyethyl methacrylate.
3. The thin flexographic cold stamping material according to claim 1, characterized in that: The modified polyepichlorohydrin is obtained by reacting POSS with epichlorohydrin.
4. A process for preparing a thin flexographic cold stamping material as claimed in any one of claims 1 to 3, characterized in that: The method comprises the following steps: firstly coating a release coating on the base film layer and then drying it, then coating an imaging layer coating on the release coating and then drying it, then vacuum-plating aluminum on the imaging layer, and finally coating an adhesive layer coating on the aluminum-plated layer and then drying it to form a thin flexographic cold stamping material.
5. The method for preparing a thin flexographic cold stamping material according to claim 4, characterized in that: The preparation method of the imaging layer coating is as follows: Under inert gas protection, 30-40 parts by mass of composite acrylic resin, 6-12 parts by mass of modified polyepichlorohydrin, 0.2-0.3 parts by mass of pigment, 3-4 parts by mass of ethanol, 47-48 parts by mass of water, 2-3 parts by mass of coupling agent, 2-3 parts by mass of nano-silicon dioxide, and 0.08-0.12 parts by mass of emulsifier are charged into a reaction container, and a high-speed homogenizer is used to disperse the ink at 500-700 r / min for 10-20 min until the ink is uniformly mixed, and then the temperature is raised to 69-71°C, stirred for reaction for 4.5-5.5h, cooled to room temperature, and adjusted to pH 8.0-9.0 by adding 25%-28% ammonia water to obtain an imaging layer coating.
6. The method for preparing a thin flexographic cold stamping material according to claim 5, characterized in that: The coupling agent includes silane coupling agent KH-560.
7. The method for preparing a thin flexographic cold stamping material according to claim 5, characterized in that: The preparation steps of the composite acrylic resin are as follows: 0.4-0.6 parts by weight of 2,4,6-tri(allyloxy)-1,3,5-triazine, 0.06-0.08 parts by weight of acrylic acid, 0.08-0.12 parts by weight of butyl acrylate, 2-3 parts by weight of diallylamine hydrochloride, 2-3 parts by weight of methyl methacrylate, and 2-3 parts by weight of hydroxyethyl methacrylate are uniformly mixed to obtain a monomer mixture; 25-35% of the monomer mixture, 0.002-0.0024 parts by weight of initiator and 30-50 parts by weight of isopropanol were stirred and mixed, and the temperature was raised to reflux while stirring. Subsequently, the remaining monomer mixture, 0.008-0.0096 parts by weight of initiator and a mixture of 30-50 parts by weight of isopropanol were added dropwise. After 1.8-2.2 hours, the addition was stopped, and the reaction was continued by keeping the temperature for 3 hours. Ammonia water with a concentration of 25%-28% was added to adjust the pH to 8.0-9.0 to obtain a composite acrylic resin.
8. The method for preparing a thin flexographic cold stamping material according to claim 5, characterized in that: The preparation method of the modified polyepichlorohydrin is as follows: 92-94 parts by weight of heptaphenylsilsesquioxane trisilanol and 500 parts by weight of solvent dichloromethane are stirred and mixed for 1-3 hours until the heptaphenylsilsesquioxane trisilanol is dissolved, 70.6-71 parts by weight of catalyst boron trifluoride ether is added at room temperature and stirred for 30 minutes, then the temperature is lowered to 17.5-18.5° C., 93-372 parts by weight of epichlorohydrin are added dropwise, and the addition is completed within 1.8-2.2 hours, then the temperature is raised to 39-41° C. and stirred for reaction for 4 hours, then the mixture is washed with a saturated sodium bicarbonate solution until it is alkaline, and then washed with deionized water until it is neutral, and the unreacted catalyst is removed, and then the mixture is distilled under reduced pressure at 109-111° C. for 1.8-2.2 hours to remove the solvent and small molecule compounds to obtain the modified polyepichlorohydrin.
Citation Information
Patent Citations
Room-temperature-curable high-temperature-resistant polyurethane sealing material and preparation method thereof
CN104861143A
Acrylic resin for release layer-free hot stamping alumite, preparation method and application thereof
CN109651559A
Multifunctional cold transfer gold stamping film and manufacturing process thereof
CN112060796A
Acrylic resin composition
KR1020050026869A
Cited By
Flexographic printing and cold stamping holographic anti-counterfeiting foil with low transfer defects and preparation method of flexographic printing and cold stamping holographic anti-counterfeiting foil
CN120902451A